Perubahan FÄ±tokÄ±mÄ±a Kecambah Kembang Kol (Brassica oleraceae L., var. botrytis) sebagai Respons terhadap Cahaya Biru - Mohamad Agus Salim (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The aim of this study was to observe the use of blue light on phytochemical changes during cauliflower (Brassica oleraceae L., var. botrytis) germination and the correlation between the parameters measured. The treatment was in the form of giving blue light and dark conditions as a control. Measurement of phytochemical compounds including ascorbic acid, glucosinolates, isothiocyanates and myrosinase enzymes was carried out every day for 5 days of germination. This research method is experimental research. Data obtained from measurements for all parameters are presented in the form of mean Â± standard error. Furthermore, all data were analyzed using analysis of variance (ANOVA). To determine differences between groups, Duncan's multiple range test (DMRT) was used at the 95% confidence level. All data analysis used SPSS software version 24.0 (IBM, Chicago, IL, USA). In addition, the measurement of the correlation between parameters is carried out using the Pearson rank correlation coefficient. The results showed that blue light treatment significantly increased all measured phytochemical parameters. A significant positive correlation occurred between myrosinase activity and isothiocyanate formation. The glucosinolate content of cauliflower sprouts remained high during observations in the blue light treatment compared to the dark conditions. Blue light induces isothiocyanate formation and higher myrosinase activity when compared to dark conditions. The conclusion from this study is that blue light significantly increases the phytochemical changes of cauliflower sprouts. Keywords: Ascorbic Acid, Glucosinolate, Isothiocyanate, Correlation, Myrosinase